Lebah dan Madu dalam Surah An-Nahl: Bees and Honey in Surah An-Nahl - Lumbantobing, Haidar Edward; Nirwana, Andri (Sekolah Tinggi Ilmu Al-Quran Isy Karima Karanganyar, 2023)
ABSTRACT Bees are Allah's creatures that are so amazing, many of Allah's gifts are given to them, even Allah glorifies bees and makes them one of the names for a letter in His book, namely Surah An-Nahl. Surah An-Nahl is a letter that was mostly revealed in Makkah, there are many themes and the essence of the letter, one of which is about the form of God's love for His creatures that must be accepted willingly and gratefully so that the creature itself gets happiness in this world and in the hereafter. In Surah An-Nahl there are two verses that tell about bees, namely verse 68 about how bees get the inspiration to make their hive so extraordinary and verse 69 about how bees can take the road to find food and produce drinks that can be a cure for humans. Honey is a drink full of properties, even the Prophet ï·º really liked it and recommended it for treatment. By using the literature study method, this research will discuss Surah An-Nahl, bees and honey so that it can be useful for humans, especially believers. Keywords: bees, honey, an-nahl